The image of agriculture in two Ciskeian communities - Webb, Nigel L (Rhodes University, Faculty of Science, Department of Geography, 1980)
Agriculture is a complex cultural institution. This is particularly the case when studying subsistence conditions in a tribal system, because aspects requiring investigation include social, religious, political and economic factors (Dalton, 1967). These factors represent an extremely broad sphere of inquiry and the large number of relevant aspects has been the cause of problems plaguing attempts to develop subsistence agriculture (Grigg, 1973). The purpose of this study is to outline an environmental perception approach to agriculture and explore the contribution that the approach could make to agricultural improvement. As such it represents a pilot study which attempts to introduce behavioural science research into agricultural development. Foster (et all (1965) outline three research foci in this respect; the socio-cultural-psychological system of the recipient people (farmers), the system of the innovating organization, and the interaction of the two. This study deals with the first focus outlined by Foster, and aims to make a statement about the image that two semi-subsistence communities have of their agricultural system. In other words, how their agricultural system appears to them.
Keywords: Urban agriculture -- Eastern Cape; Land use, Urban -- South Africa -- Eastern Cape; Agriculture -- South Africa -- Eastern Cape; Urban agriculture